Topeng Pajegan sebagai Media Penerangan Agama Hindu - Gde Puasa, I Made (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
Pajegan Mask is one of the many arts in Bali. Pajegan Mask Dance is a performance art which in its performance is a symbol of human life that talks about life and human behavior and character. The Pajegan Mask performance is motivated by the Pajegan Mask Performance as a guardian, bebali and balih-balihan whose roles still need to be improved as a medium for illuminating Hinduism.Based on this, what will be discussed in this paper include: (1) The form of the Pajegan Mask Performance as a medium for illuminating Hinduism. (2) The function of the Pajegan Mask Performance functions as a medium for illuminating Hinduism. (3) The meaning contained in the Pajegan Mask Performance as a media for the illumination of Hindu religion.Analiisis Pajegan Mask dance form shows the physical understanding of a work of art that functionally contains life characteristics related to religious rituals, while the form of Pajegan Mask Dance performance consists of: (1 ) The form of Pajegan Mask Dance performance, (2) the Pajegan Mask performance function, namely: (1) Communication and information media, (2) Entertainment media, (3) Social criticism function. The meanings of the Pajegan Mask are: (1) The religious and social meaning, (2) The spiritual meaning. So the Pajegan Mask Dance performance is not only used as a ritual complement in Hindu religious ceremonies, but its role really needs to be maximized and enhanced as a medium for illuminating Hinduism.